From best to worst? Romania and its nostalgia for Olympic successes - Petracovischi, S.; Terret, T. (International Journal of the History of Sport, 2013)
While the Los Angeles Olympic Games in 1984 constituted Romania's best performance ever, 2012 London Olympic Games were characterised by the worst performance in its history. During the time between these two events, the country went from being a communist regime to a liberal government. This transition invites consideration of the transformation Romania's sports policy underwent and its repositioning with regard to the Olympic Movement, both before and after the 1989 turning point. Analysis suggests that, in failing to professionalise Romanian sport, the Romanian Olympic and Sports Committee (COSR) was tempted to readopt a model of state-financed sport, with the aim of reinstating the nation to its former position among the world's sporting elite. Research gate: https://www.researchgate.net/publication/263065736_From_Best_to_Worst_Romania_and_Its_Nostalgia_for_Olympic_Successes